Clinical Profiles of Placenta Accreta Spectrum: The PACCRETA Population-based Study. Issue 2 (24th June 2022) - Kayem, G.; Seco, A.; Beucher, G.; Dupont, C.; Branger, B.; Creen Herbert, C.; Huissoud, C.; Freeson, J.; Winer, N.; Langer, B.; Rozenberg, P.; Morel, O.; et al.
Abstract : ( BJOG . 2021;128:1646–1655) Placenta accreta occurs when a placenta attaches too deeply into the uterine wall. Placenta increta and percreta are more severe forms where the placenta embeds further into the uterine myometrium or grows through the uterus to other nearby organs. All three of these conditions are included in placenta accreta spectrum or PAS. The major complications of PAS include the placenta not being able to normally deliver leading to heavy bleeding and potential hysterectomy. PAS is a major cause of maternal mortality and morbidity and occurs in 1.7 to 4.6 per 10, 000 deliveries. Due to the rise in cesarean deliveries (CD) the rate of PAS has been reported as high as 90 per 10, 000 in recent years.